Stratospheric ozone depletion and future levels of atmospheric chlorine and bromine - Prather, Michael J; Watson, Robert T (Nature, 1990)
The rise in atmospheric chlorine levels caused by the emission of chlorofluorocarbons and other halocarbons is thought to be the main cause of the appearance of the Antarctic ozone 'hole' in the late 1970s, and the more modest ozone depletion observed over parts of the Northern Hemisphere. Atmospheric bromine, also associated with halocarbon emissions, is believed to contribute to ozone depletion. Over the next decade, further increases in these compounds are inevitable. Model calculations show that by the end of the next century, atmospheric chlorine and bromine levels may return to those prevalent before the onset of the ozone hole, but only if more stringent regulations are applied to halocarbon production than those currently proposed. © 1990 Nature Publishing Group.